PRAKTIK AGROFORESTRI TRADISIONAL (LAMPOH) DI ACEH BESAR: MENILAI POTENSI DAN PEMANFAATAN OLEH MASYARAKAT DI KECAMATAN SIMPANG TIGA - Durrah Hayati; Fahmy Armanda; Maryam Jamilah; Ida Rosita; Ali Muhammad Muslih (Politeknik Pertanian Negeri Samarinda, 2023)
Traditional agroforestry systems (TAFS) are longstanding practices characterized by the absence of intentional agricultural intensification. In Aceh, Indonesia, a specific type of TAFS known as